Emerging ionic liquid engineered polymeric membrane for carbon dioxide removal: A review - Shafie, S.N.A. (Elsevier B.V., 2022)
Ionic liquid (IL), which possesses excellent properties such as high affinity towards carbon dioxide (CO2), negligible vapour pressure and highly viscous is a promising material to be incorporated in membrane gas separation. As conventional membranes carry limitations that hinder the separation performance, the presence of IL has the potential to overcome the problem. However, with the incorporation of IL, membrane stability, high pressure condition application and mechanical strength are among the major drawbacks for IL based membranes. Therefore, this review highlights the progress in IL-enhanced membrane for gas separation application. The progress on IL-enhanced membrane such as supported ionic liquid membrane (SILM), poly(RTIL) membrane, polymer-ionic liquid blend membrane, ionic liquid mixed matrix membrane (IL-MMM) are also critically review in this work. The advantages and challenges associated with the membranes are thoroughly discuss in this review. The performance of IL-based membranes is also plotted against Robeson Upperbound to show the progress of the IL based membrane over the years. Finally, the opportunities for the IL based membranes are deliberate for future development in gas separation. Â© 2022 Elsevier B.V.